HONORARY FELLOW - M.M. PAYAK - PAYAK, M.M. (Indian Phytopathology, 2002)
Prof. M.M. Payak was born on May 15, 1928. He did his B.Sc. from Agra University, Agra and M.Sc. (Agric.) from Banaras Hindu University, Varanasi in 1949. He was awarded Degree of Doctor of Philosophy from University of Pune in 1958. He joined as Research Assistant in 1951 at Maharashtra Association for Cultivation of Sciences (MACS), Pune and as demonstrator in Deptt. of Botany University of Pune in 1953. He was appointed as Junior Research Assistant (Mycologist) at IARI Regional Station, Shimla in 1958 and was appointed as Plant Pathologist and Principal Investigator, IARI, New Delhi in 1965. He subsequently became Maize Pathologist in 1970. He joined as Head, Division of Mycology and Plant Pathology, IARI, New Delhi in 1983 and as Sr. Maize Pathologist in 1986. He continued his association with Plant Pathology after his retirement and was appointed as Emeritus Scientist, at NBPGR, New Delhi in 1989.